2014
DOI: 10.3389/fpsyg.2014.00531
|View full text |Cite
|
Sign up to set email alerts
|

Gated auditory speech perception: effects of listening conditions and cognitive capacity

Abstract: This study aimed to measure the initial portion of signal required for the correct identification of auditory speech stimuli (or isolation points, IPs) in silence and noise, and to investigate the relationships between auditory and cognitive functions in silence and noise. Twenty-one university students were presented with auditory stimuli in a gating paradigm for the identification of consonants, words, and final words in highly predictable and low predictable sentences. The Hearing in Noise Test (HINT), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 84 publications
6
39
0
Order By: Relevance
“…All of these factors have been linked to changes in attentional control (e.g., Hartman & Hasher, 1991) and recruitment of prefrontal cortex (Bishop, 2009). These findings align with the emerging evidence that speech processing ability in challenging environments is associated with working memory capacity (Moradi, Lidestam, Saremi, & Rönnberg, 2014;Rönnberg, Rudner, Lunner, & Zekveld, 2010;Zekveld, et al, 2013). Working memory capacity, which predicts performance of not only language processing tasks but also a wide variety of higherorder cognitive assessments, has been argued to index executive attention that regulates the information content activated in the memory (for a review, see Engle, 2002).…”
Section: Ganong Effect and Speech-in-speech Processing Is Associated supporting
confidence: 79%
“…All of these factors have been linked to changes in attentional control (e.g., Hartman & Hasher, 1991) and recruitment of prefrontal cortex (Bishop, 2009). These findings align with the emerging evidence that speech processing ability in challenging environments is associated with working memory capacity (Moradi, Lidestam, Saremi, & Rönnberg, 2014;Rönnberg, Rudner, Lunner, & Zekveld, 2010;Zekveld, et al, 2013). Working memory capacity, which predicts performance of not only language processing tasks but also a wide variety of higherorder cognitive assessments, has been argued to index executive attention that regulates the information content activated in the memory (for a review, see Engle, 2002).…”
Section: Ganong Effect and Speech-in-speech Processing Is Associated supporting
confidence: 79%
“…These words were selected from the 46 Swedish monosyllabic words (e.g., bad, dus, gap, jul, ram, sot, and väck) used by Moradi, Lidestam, and Rönnberg (2013) and Moradi et al. (2014).…”
Section: Methodsmentioning
confidence: 99%
“…(2013, 2014). Each sentence was either an LP or HP sentence, according to how predictable the last word in each sentence was.…”
Section: Methodsmentioning
confidence: 99%
“…It is difficult to know if and to what extent variations along these dimensions affect the relationship to cognition, and whether these variations may explain, at least in part, inconsistencies between studies. For instance, could differences in target speech help explain why some studies (Desjardins and Doherty 2013;Moradi et al 2014), using a complex sentence perception test, found a significant correlation between reading span and intelligibility, while another study (Kempe et al 2012), using syllables and the same cognitive test, did not? The goal of this study is to systematically vary the complexity of the listening situation and to investigate how this variation affects the relationship between intelligibility and assorted cognitive measures.…”
Section: Introductionmentioning
confidence: 99%